The stakeholder perspective : relationship management to increase value and success rates of complex projects - Pirozzi, Massimo (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
The Stakeholder Perspective places people at the center of both projects and project management. It gives to the project management community a helpful, innovative, stakeholder-centered approach to increase projects' delivered value and success rate. It presents a logical model also called the "Stakeholder Perspective," which acts as the reference point in a structured path to effectiveness. Starting from the analysis of a project's stakeholders, the model integrates both rational and relational innovative approaches. Its continuous focus on stakeholder requirements and expectations helps to set a proper path, and to maintain it, in order to target success and to achieve goals in a variety of projects with different size and complexity. The book presents a set of innovative and immediately applicable techniques for effective stakeholder identification and classification, as well as analysis of stakeholder requirements and expectations, key stakeholders management, stakeholder network management, and, more generally, stakeholder relationship management. The proposed stakeholder classification model consists of just four communities, each one based on the commonality of main interests and behavior. This model features an accurate and stable identification process to increase effective communication and drastic reduce relationship complexity. A systemic approach is proposed to analyze both stakeholder requirements and expectations. The approach aids in detecting otherwise unclear stakeholder requirements and/or hidden stakeholder expectations. An interactive communication model is presented along with its individual and organizational frames of reference. Also presented are relevant cues to maximize effective and purposeful communication with key stakeholders as well as with the stakeholder network. The importance of satisfying not only the project requirements but also the stakeholder expectations is demonstrated to be the critical success factor in all projects. An innovative approach based on the perceived value and key performance indicators shows how to manage different levels of project complexity. The book also defines a complete structured path to relationship effectiveness called "Relationship Management Project," which can be tailored to enhance stakeholder and communication management processes in each one of the project management process groups (i.e. initiating, planning, executing, monitoring and controlling, and closing). The book concludes with a look ahead at Project Management X.0 and the stakeholder-centered evolution of both project and portfolio management.
Part I. THE STAKEHOLDER PERSPECTIVEChapter 1. Stakeholders, Who Are They?Chapter 2. The Recent Central Role of Stakeholders in Project ManagementChapter 3 Stakeholder Identification: Integrating Multiple Classification and Behavioral ModelsChapter 4. Effective Stakeholder Analysis: A Systemic ApproachChapter 5. Key Stakeholders Management: Principles of Effective Direct CommunicationChapter 6. Stakeholder Network Management: Informative and Interactive CommunicationChapter 7. Basic Personal and Interpersonal Skills: Personal Mastery, Leadership, TeamingChapter 8. Ethics in Stakeholder Relations Part II. THE RELATIONSHIP MANAGEMENT PROJECTChapter 9. Stakeholder Relations and Delivered Value: An Indissoluble LinkChapter 10. Satisfying Stakeholder Requirements and Expectations: The Critical Success FactorChapter 11. Facing Successfully Different Levels of Project Complexity Chapter 12. Targeting Both Project and Business Value Generation by Using KPIsChapter 13. Relationship Management Project: A Structured Path to EffectivenessChapter 14. New Stakeholder-Centered Trends: Project Management X.0
OCLC-licensed vendor bibliographic record.
Keywords: Project management; BUSINESS & ECONOMICS / Project Management; COMPUTERS / Information Technology; TECHNOLOGY / Engineering / General